Soliton orthogonal frequency division multiplexing with phase–frequency coding on the base of inverse scattering transform - Bogdanov, Stepan A.; Frumin, Leonid L. (Journal of inverse and ill-posed problems, 2021)
We propose a method for increasing the speed and spectral efficiency of information transmission over soliton communication lines, based on algorithms for solving inverse and direct scattering problems, in the frame of a modern soliton orthogonal frequency division multiplexing (SOFDM) approach. The proposed method uses a simultaneous phase and frequency coding. This phase–frequency coding method retains all the technological advantages of the SOFDM method, and due to the additional frequency coding, a noticeable increase in the information transfer rate over the soliton optical lines is expected. Numerical modeling confirmed the proposed method for telecommunication applications’ prospects.